LIVE KINEMATIC MODELS IN MATHCAD - Valery F. Ochkov (Открытое образование (Москва), 2016)
The paper considers creating animation of different kinematical devices in mathematical package Mathcad (steam engine, windscreen wipers, walking machine). Mathematical tools for solving algebraic equations and their systems are described.